Pengembangan Badan Usaha Milik Desa (BUMDes) Mitra Karya Sejahtera di Desa Toapaya Selatan Kabupaten Bintan - Riska Sulistyani; Afrizal Afrizal; Uly Sophia (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2024)
The establishment of Village-Owned Enterprises is a way to innovate in improving village development, especially in the economic sektor. The reality is that many villages are not ready to manage and even develop BUMDes. This research aims to find out how the development strategy carried out by BUMDes Mitra Karya Sejahtera as one of the BUMDes with developing status in Bintan Regency. The type of research used is descriptive research with a qualitative approach. Then the data collection technique was carried out by interview, documentation and observation.The results show that this BUMDes does not have a clear mechanism in identifying problems, and problems are often handled traditionally through deliberation. The main obstacles in the development of BUMDes business units include the impact of the Covid-19 pandemik, limited capital, and less strategic business locations. While development strategies such as legal entity registration and organizing events have been proposed, implementation has not been optimal. BUMDes have made efforts to realize the strategies, including capital strengthening, HR training, and expansion of business units. However, the impact of these efforts is still not maximized due to limitations in implementation and unsustainable activities. Effective monitoring and evaluation have also not been implemented, given that evaluations are conducted informally and unscheduled.